1976
DOI: 10.1002/aic.690220321
|View full text |Cite
|
Sign up to set email alerts
|

The steady and unsteady state analysis of a simple gas centrifuge

Abstract: The operating theory of the gas centrifuge is developed under both steady and unsteady state behavior. It is shown that countercurrent flow patterns in a gas centrifuge enhance the possible separation. The effect of self‐diffusion of the gaseous mixtures is shown to be significant with low molecular weight gases but of less significance with heavy gases such as uranium isotopes. The time required to develop steady state pressure and concentration profiles is in the order of minutes, even with no net flow to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Previous studies of centrifugal gas separation always stress that the process is dependent purely on molecular weight difference (unlike others such as differential diffusion). , This is true for extreme cases such as the isotopic case presented in Figure b. However from a stream recovery viewpoint the situation is more complex.…”
Section: Equilibrium Profilesmentioning
confidence: 95%
“…Previous studies of centrifugal gas separation always stress that the process is dependent purely on molecular weight difference (unlike others such as differential diffusion). , This is true for extreme cases such as the isotopic case presented in Figure b. However from a stream recovery viewpoint the situation is more complex.…”
Section: Equilibrium Profilesmentioning
confidence: 95%
“…The somewhat later work of Groth and Beyerle 6 also concentrated on gaseous isotopic separation. Two notable exceptions to the isotopic studies were the works of Williams, who examined the potential for syngas separation, and Auvil and Wilkinson, who were motivated by problems with acid rain in the 1970s. There have been occasional literature reports geared toward the separation of unusual isotopes, e.g., SiF 4 for wafer manufacture, and the preparation of unusual tin and chromium isotopes.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Very little work was geared toward application for the separation of other more standard gas mixtures. 5,6 Recently, we have shown that the assumptions applicable to isotope separation were not valid for centrifugal separation of lighter gases 7 sindeed, the possibility of higher-pressure operation and higher throughputs could be more readily tackled than for heavier gases. 8,9 In this work, we address one of the assumptions inherent in all previous analyses of the time-dynamical behavior of the separation process in a gas centrifuge, namely, that net convective flux can be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses of the gas centrifuge were almost exclusively oriented toward its application for isotope enrichment using the gas UF 6 . Very little work was geared toward application for the separation of other more standard gas mixtures. , Recently, we have shown that the assumptions applicable to isotope separation were not valid for centrifugal separation of lighter gases 7 indeed, the possibility of higher-pressure operation and higher throughputs could be more readily tackled than for heavier gases. , In this work, we address one of the assumptions inherent in all previous analyses of the time-dynamical behavior of the separation process in a gas centrifuge, namely, that net convective flux can be neglected. In any realistic scenario, this is not the case because, during the process of gas component separation in a centrifuge, the motion of the molecules arises from various forces.…”
Section: Introductionmentioning
confidence: 99%